Fly ash as partial cement replacement in producing high flexural hollow section beam - Nurshadahtika, Abdul Razak (2014)
Flexural and ultimate load behavior of hollow concrete beams under one point load is discussed in this research. This research deals with agricultural waste of fly ash in terms of partial cement replacement in hollow section beam. Concrete is both dominant as a construction material and contributor to greenhouse gas emissions due to cement manufacturing. Therefore, replacing Portland cement with fly ash reduces greenhouse gas emissions. In this research, reinforced hollow section beam in rectangular with size 250 mm x 300 mm with 2000 mm length is designed to resist a point load of 50 kN. The percentage proportion testing and curing test is fixed with 30% of fly ash by weight of with 7, 14, and 28 days respectively. Three types of reinforced hollow section beams were constructed in this research which has three different size of the cavity of Bi (40 mm x 100 mm), B2(50 mm x 100 mm) and 133(60 mm x 100 mm) along together with one solid beam without hollow part. From this research, the highest ultimate load achieved is specimen 131. Specimen B3 with fly ash content up to 30 % cement replacement resulted in higher load-deflection ratio and proved to be the suitable cavity size in producing high flexural hollow section beam.